Framework Pengembangan Produk Turunan Tape menjadi Tape Kit sebagai Bagian dari Petualangan Rasa dan Wisata Kultura di Desa Banjarsari Berbasis Income Generating - Iriaji, Iriaji; Taufani, Agusta Rakhmat; Roekhan, Roekhan; Hamdani, Ardiansyah Yusuf; Nazwa, Venina Nabilla (VISA: Journal of Vision and Ideas, 2025)
Banjarsari Village has superior potential as a center for traditional tape production, but its conventional processing is a challenge in attracting tourists and the younger generation. This research aims to design a framework for the development of tape derivative products into Tape Kits as part of flavor and cultural tourism innovations that are oriented towards increasing community income (income generating). The approach used is qualitative with a case study method, where the community is actively involved through the stages of training in making Tape Kits, assistance in the packaging and marketing process, to the preparation of promotional strategies targeting the tourism sector. Data collection techniques include participatory observation, in-depth interviews with local business actors, and visual and narrative analysis of product design and promotional strategies. The results show that Tape Kit has not only succeeded in expanding the appeal of tape as a distinctive souvenir, but is also able to integrate local cultural values in the form of innovative presentations. In addition, the active participation of the community in the production and promotion process also encourages the birth of a sustainable new business ecosystem. This framework is expected to be replicated in other areas that have local culinary potential as a cultural tourism-based economic lever.